PENGARUH MODEL PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION TERHADAP KEMAMPUAN BERPIKIR KRITIS DENGAN POLA LESSON STUDY - Nuraini, Nuraini; Muliawan, Wawan; Darwilin, Darwilin (UNIVERSITAS HAMZANWADI, 2020)
The purpose of this research is to know the Influence The Effect of Cooperative Learning Model Investigation Group (IG) Toward Critical Thinking Ability With Lesson Study Pattern on Biology Subject Class X MAN Selong . The type of this research is experimental research using Quasy Experimental Design. The population in this study are students of class X IPA Semester II consisting of 3 classes with a total of 91 students. The sample in this research is IPA 1 class as experimental class and IPA 2 class as control class using simple random sampling technique. The instrument in this research is the critical thinking skill test in the form of essay test which amounts to 7 items. Based on the data analysis, the average value of post-test experimental class is 83.00 and control class is 67.70. Meanwhile, hypothesis test using statistical analysis with the t-test formula at the level of 5% confidence is obtained tcount of 14.97. After comparison with ttable 2.056, tcount 14.97> ttable 2.056, so the conclusion in this research is The Effect Cooperative Learning Model Type Investigation Group (IG) Influential on Critical Thingking Ability With Lesson Study Pattern on Biology Subject Class X MAN Selong. Keywords: Investigation Group, Critical Thinking Skill, Lesson Study